Paul on the Human Vocation : Reason Language in Romans and Ancient Philosophical Tradition. - Dürr, Simon (Berlin/Boston : Walter de Gruyter GmbH, 2021)
The series Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft (BZNW) is one of the oldest and most highly regarded international scholarly book series in the field of New Testament studies. Since 1923 it has been a forum for seminal works focusing on Early Christianity and related fields. The series is grounded in a historical-critical approach and also explores new methodological approaches that advance our understanding of the New Testament and its world.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books